Thermoregulatory sex differences among surfers during a simulated surf session - Skillern, N. P.; Nessler, J. A.; Schubert, M. M.; Moore, B.; Newcomer, S. C. (Sports Engineering, 2021)
The purpose of this study was to test the hypothesis that under controlled surf conditions, sex differences in skin temperature exist, but core temperature would not vary between sexes when performing a simulated surf session while wearing a 2-mm wetsuit. Twenty male and 13 female surfers engaged in a 60-min simulated surf protocol using a custom 2-mm wetsuit in an Endless Pool Elite Flume with water temperature set to 15.6 °C. Participants were instrumented with a heart rate monitor, eight skin temperature sensors, and a disposable sensor for measurement of core temperature. The surf simulation consisted of paddling, duck-diving and stationary activities at three paddling speeds (1.2, 1.4 and 1.6 m/s). Participants were asked their thermal sensation periodically during the protocol, and all data were collected at 1-min intervals. Results indicated no significant differences in core temperature between males (37.31 ± 0.35 °C) and females (37.32 ± 0.48 °C, p = 0.995). Upper arm and thigh skin temperatures were significantly lower in females (27.45 ± 1.04 °C and 23.53 ± 0.78 °C, respectively) than males (28.61 ± 1.32 °C and 24.73 ± 0.68 °C; p = 0.012 and p = 0.000, respectively). Conversely, skin temperatures in the abdomen were significantly lower in males (26.57 ± 1.44 °C) than females (27.75 ± 1.50 °C; p = 0.035). Meanwhile, perceptual data were inconclusive. The results suggest that although regional differences in skin temperature may exist between male and female surfers, they may be too small to translate into perceptual differences and are unnecessary when considering wetsuit design.